Предмет: Алгебра, автор: Amsterdamus

Упростите sin^4(x)-cos^4(x)-sin^2(x)+cos^2(x)

Ответы

Автор ответа: ShirokovP
0
    sin^4x - cos^4x - sin^2x + cos^2x = 
= (sin^2x)^2 - (cos^2x)^2 - (sin^2x - cos^2x) = 
= (sin^2x - cos^2x) * (sin^2x + cos^2x) - (sin^2x - cos^2x) = 
Вспомним, sin^2x + cos^2x = 1 ==> 
(sin^2x - cos^2x) * 1  - (sin^2x - cos^2x) = 
sin^2x - cos^2xsin^2x + cos^2x = 
=  0 

Примечание
sin^2x и  - sin^2x, а также cos^2x и - cos^2x взаимно уничтожились 
Похожие вопросы
Предмет: Математика, автор: Bogdan2008qwer